Implementasi Nilai Kesabaran Dalam Pendidikan Karakter: Perspektif Tafsir Surat Al-Asr - Qomari, Vikri Aflaha; Ghofur, Abdul (Universitas Negeri Padang, 2024)
Character education plays a crucial role in shaping an individual's personality and morality, especially amidst the increasingly complex challenges of the modern era. One of the key values in character education is patience. Thus, integrating the value of patience into character education is essential, particularly in addressing modern challenges. Therefore, this study aims to explore the implementation of patience values in character education from the perspective of Surah Al-’Asr. This research is qualitative, using a literature study method with a tahlili interpretation approach to analyze the significance of patience in character education. It highlights the importance of time, good deeds, and mutual counsel in truth and patience. The findings indicate that instilling the value of patience can equip individuals to be disciplined in managing time, perform good deeds, restrain desires, and accept Allah's decrees with contentment. Ultimately, the implementation of patience values contributes to the development of strong and moral character in individuals. This study aims to provide insights and make a significant contribution to the field of Islamic education while emphasizing the importance of integrating moral and ethical values into character education in accordance with the National Education Law